Protective Effect of Joa-Gui Em through the Improvement of the NLRP3 and TLR4/NF-κb Signaling by Ischemia/Reperfusion-Induced Acute Renal Failure Rats. (28th May 2021) - Na, Se Won; Jang, Youn Jae; Hong, Mi Hyeon; Yoon, Jung Joo; Lee, Ho Sub; Kim, Hye Yoom; Kang, Dae Gill
Abstract : Joa-gui em (左歸飮, JGE) is known to be effective for treating kidney-yin deficient syndrome. However, there is a lack of objective pharmacological research on improving kidney function. This study was designed to evaluate whether JGE improves renal function and related mechanisms in rats with acute renal injury induced by ischemia/reperfusion (I/R). The acute renal failure (ARF) group was subjected to reperfusion after inserting a clip into the renal artery for 45 min. The ARF + JGE (100 or 200 mg/kg/day) groups were orally administered for four days after their I/R surgery, respectively. JGE treatment suppressed the increase in kidney size in the ARF animal model and alleviated the polyuria symptoms. In addition, to confirm the effect of improving the kidney function of JGE, lactate dehydrogenase levels, blood urea nitrogen/creatinine ratio, and creatinine clearance were measured. As a result, it decreased in the ARF group but significantly improved in the JGE group. Also, as a result of examining the morphological aspects of renal tissue, it was shown that JGE improved renal fibrosis caused by ARF. Meanwhile, it was confirmed that JGE reduced inflammation through the nucleotide-binding oligomerization domain-like receptor pyrin domain containing-3 (NLRP3) and toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF- κ B) signaling pathways, which are the major causes of acute ischemic kidney injury, thereby improving renal function disorder. The JGE has a protective effect by improving the NLRP3 and TLR4/NF- κ B signaling pathway in rats with acute renal dysfunction induced by I/R injury.